Varied Assessments Used to Measure Students’ Achievement in Introduction to Literature Class - Nurul Ain (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2019)
This paper reported types of assessments and assessment practices used in Introduction to Literature (ITL) class. Looking at the context and the purpose of the assessment, the principles of classroom learning are to be applied in planning, constructing and administering the tests. The test was also constructed to contain a representative sample of the course, the relationship between the test items and the course objectives to keep up with the content validity. The test has two forms of assessment as dealt in learning contract that are spoken and written forms. The results of students’ assessment can be categorized into several categories: the first category is the students who have good achievement both in spoken and written performances; the second one is for category which the students have great range of different between spoken and written performances; the third category is the students who have the little range of differences between spoken and written performances; and the last category is the students who have got fair achievement both in spoken and written performances.